2014
DOI: 10.4238/2014.april.25.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of okra (Abelmoschus esculentus L.) by inter-simple sequence repeat (ISSR) markers

Abstract: ABSTRACT. Okra (Abelmoschus esculentus L.) is not only a nutrientrich vegetable but also an important medicinal herb. Inter-simple sequence repeat (ISSR) markers were employed to investigate the genetic diversity and differentiation of 24 okra genotypes. In this study, the PCR products were separated by electrophoresis on 8% nondenaturing polyacrylamide gel and visualized by silver staining. The 22 ISSR primers produced 289 amplified DNA fragments, and 145 (50%) fragments were polymorphic. The 289 markers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
2
16
0
2
Order By: Relevance
“…Gene diversity and Shannon's information index of retrotransposon markers were lower than that of SSR markers, which demonstrated that microsatellites are more powerful markers for the identification of a variety. The values of genetic diversity, Shannon's information index, and PIC in our study were comparable with those reported by Yuan et al (2014) using ISSR markers. PIC value reflects the level of genetic diversity in a population.…”
Section: Discussionsupporting
confidence: 88%
“…Gene diversity and Shannon's information index of retrotransposon markers were lower than that of SSR markers, which demonstrated that microsatellites are more powerful markers for the identification of a variety. The values of genetic diversity, Shannon's information index, and PIC in our study were comparable with those reported by Yuan et al (2014) using ISSR markers. PIC value reflects the level of genetic diversity in a population.…”
Section: Discussionsupporting
confidence: 88%
“…Molecular markers are seen as an important additional tool in germplasm characterization studies, since they are minimally influenced by environmental conditions or plant development factors (Schafleitner, Kumar, Lin, Hegde, & Ebert, 2013). In the case of okra, several molecular markers have been used for germplasm characterization, e.g., random amplified polymorphic DNA (RAPD; Martinello, Leal, Amaral Júnior, Pereira, & Daher, 2003), inter-simple sequence repeat (ISSR; Yuan et al, 2014), amplified fragment length polymorphism (AFLP; Kyriakopoulou et al, 2014), and simple sequence repeats (SSR; Kumar et al, 2017a). The AFLP markers, in spite of being dominant, have several advantages, such as broad genome coverage, cost-effectiveness, reproducibility, and independence of sequence information (Zhang, van Parijs, & Xiao, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on okra have mainly focused on genetic breeding, cultivation techniques, nutritional components, and medicinal efficacy [ 22 , 23 , 24 , 25 , 26 ]. Most of the molecular biology studies on okra were based on molecular markers, such as inter-simple sequence repeat (ISSR) and sequence-related amplified polymorphism (SRAP) markers, to analyze the genetic diversity of okra germplasm resources [ 27 , 28 ]. Because the okra genome has not been sequenced, there is little published research on the identification and organ-specific expression patterns of the synthesis genes associated with the synthesis of bioactive constituents in this crop.…”
Section: Introductionmentioning
confidence: 99%